Akuntansi Merdiban (Tangga): Sejarah & Praktek Akuntansi Islam Menuju Keadilan dan Kepatuhan Illahiyah - Maulana, Bonnix Hedy (Universitas Muhammadiyah Prof. DR HAMKA., 2017)
Accounting Merdiban a historical record of accounting used by the Abbasid Caliph of Islam began to Caliph Ottoman era in the year 1924. Historical evidence proves form of financial reporting technologies in the context of the government at that time. Unlike the present context that the role of accounting in the era of the caliphate Islamiyah is more geared to meet the command and prohibition of Allah Ta'ala that is contained in the Quran and Hadith as a source of law. Through this history can be analyzed on ontology, and axiology epistimology on the accounting records of that era. This article is expected to open new horizons to the concept of Islamic accounting in order to be consistent with the purpose of man on earth is to worship Allah Ta'ala.